Melatonin protects oocyte quality from Bisphenol A‐induced deterioration in the mouse. Issue 3 (1st March 2017) - Zhang, Mianqun; Dai, Xiaoxin; Lu, Yajuan; Miao, Yilong; Zhou, Changyin; Cui, Zhaokang; Liu, Honglin; Xiong, Bo
Abstract: Bisphenol A (BPA) has been reported to adversely affect the mammalian reproductive system in both sexes. However, the underlying mechanisms regarding how BPA disrupts the mammalian oocyte quality and how to prevent it have not been fully defined. Here, we document that BPA weakens oocyte quality by impairing both oocyte meiotic maturation and fertilization ability. We find that oral administration of BPA (100 μg/kg body weight per day for 7 days) compromises the first polar body extrusion (78.0% vs 57.0%, P <.05) by disrupting normal spindle assembly, chromosome alignment, and kinetochore‐microtubule attachment. This defect could be remarkably ameliorated (76.7%, P <.05) by concurrent oral administration of melatonin (30 mg/kg body weight per day for 7 days). In addition, BPA administration significantly decreases the fertilization rate of oocytes (87.2% vs 41.1%, P <.05) by reducing the number of sperm binding to the zona pellucida, which is consistent with the premature cleavage of ZP2 as well as the mis‐localization and decreased protein level of ovastacin. Also, the localization and protein level of Juno, the sperm receptor on the egg membrane, are strikingly impaired in BPA‐administered oocytes. Finally, we show that melatonin administration substantially elevates the in vitro fertilization rate (63.0%, P <.05) by restoring above defects of fertilization proteins and events, which might be mediated by the improvement of oocyte quality via reduction of ROS levels and inhibition of apoptosis. Collectively, our data reveal that melatonin has a protective action against BPA‐induced deterioration of oocyte quality in mice.